Zumba as the selected physical activity in managing type 2 diabetes mellitus - Rozali, Mohammad Azrai; May, Khin Soe (IIUM Press, International Islamic University Malaysia, 2018)
Diabetes mellitus is defined as the persistent elevated level of sugar also known as hyperglycaemia that occurs in the body at all times (Brashers, Jones & E., 2014). Diabetes mellitus can be divided into two categories, type 1 and type 2. Although share the same clinical presentation, both type 1 and 2 differ in terms if etiology or the mechanism that cause the disease. Generally type 1 diabetes is caused by the lack of insulin circulating in the body while type 2 results from the insensitivity of the insulin receptors (Brashers et al., 2014). Identifying which types of diabetes a person has is crucial because the management is different among these two types. The frequency of diabetes type 2 is more compared to diabetes type 1 (Brashers et al., 2014). Almost 90% of people in the world who are diagnosed with diabetes mellitus and hyperglycaemia suffering from type 2 (Carver & Abrahamson, 2009). Only a fraction of the population that has diabetes mellitus has type 1. This happens because type 1 diabetes mellitus is usually congenital or idiopathic that results from autoimmune most of the time (Brashers et al., 2014). The more prevalence type 2 diabetes mellitus is caused by a larger factor which includes environmental and lifestyle. Both these two factors contribute to the development of diabetes type 2 with the latter one more significant. People who opt for a sedentary lifestyle are at a greater risk of developing type 2 diabetes mellitus (Franks, 2012) . Prior developing the disease, these people usually will have an abnormal result in the “Impaired Glucose Tolerance Test” (IGTT). Within two years, if the result is still the same or increased then they will develop type 2 diabetes mellitus (Pi-Sunyer, 2007).